Expert: No need to take Sabah issue to ICJ - New Sabah Times English, (KK) (New Sabah Times English (kk), 2013)
KUALA LUMPUR: There is no need for Malaysia to bring the issue of Sabah's rights to the International Court of Justice (ICJ) as historical and non-historical facts clearly show that it is a sovereign state of Malaysia,said historian Prof Emeritus Dr Ranjit Singh of Universiti Utara Malaysia.